1722. In vivo Activity of Imipenem/XNW4107 Human-Simulated Regimen against Serine Carbapenemase-Producing Acinetobacter baumannii and Pseudomonas aeruginosa in the Neutropenic Murine Thigh Infection Model. (15th December 2022) - Fratoni, Andrew J; Berry, Angela; Yuan, Haitao; Liu, Xiao; Chen, Xi; Wu, Yuchuan; Nicolau, David P; Abdelraouf, Kamilia
Abstract: Background: Imipenem (IPM)/XNW4107 is a novel β-lactam/β-lactamase inhibitor with i n vitro activity against serine carbapenemase-producing Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacterales. Herein, we evaluated the in vivo activity of an IPM/XNW4107 human-simulated regimen (HSR) against clinical OXA-23- and OXA-24-producing A. baumannii as well as KPC- and GES-producing P. aeruginosa using a neutropenic murine thigh infection model. Methods: Seven A. baumannii and 4 P. aeruginosa isolates were included. IPM and IPM/XNW4107 MICs (XNW4107 fixed at 8 mg/L) were tested in triplicate by broth microdilution. One thigh of neutropenic ICR mice (6 mice per group) was inoculated with ∼10 7 CFU/mL bacterial suspensions. HSR that mimicked the clinical exposures of IPM 500 mg q6h alone or in combination with XNW4107 250 mg q6h each as 1 h infusion were developed in the murine model. In efficacy studies, two hours after inoculation, placebo, IPM 500 mg q6h 1 h infusion HSR, or IPM/XNW4107 500/250 mg q6h 1 h infusion HSR were administered subcutaneously. Efficacy was measured as the change in log10 CFU/thigh at 24 h compared with 0 h controls. Results: Isolates were IPM resistant (MICs 16 - > 64 mg/L). IPM/XNW4107 A. baumannii and P. aeruginosa MIC ranges were 1-16 and 1- 8 mg/L, respectively. Across all examined isolates, 0 h mean ± SD bacterial burden was 5.86 ± 0.32 log10 CFU/thigh. The 24 h increase in bacterial burden was 2.68 ± 0.91 log10 CFU/thigh in the sham controls. IPM HSR monotherapy groups showed mean increase in bacterial burden of 2.34 ± 0.95 log10 CFU/thigh. Bacterial kill with IPM/XNW4107 500/250 mg q6h 1 h infusion HSR ranged from -0.46 ± 1.69 to -3.77 ± 0.15 and -2.33 ± 0.25 to -3.76 ± 0.57 among A. baumannii and P. aeruginosa isolates, respectively. IPM/XNW4107 500/250 mg q6h 1 h infusion HSR produced > 1-log kill against 6/7 examined A. baumannii with the exception of A. baumannii 160 (IPM/XNW4107 MIC 16 mg/L) and 4/4 P. aeruginosa as well as > 2-log kill against 4/7 A. baumannii and 4/4 P. aeruginosa . Conclusion: IPM/XNW4107 500/250 mg q6h 1 h infusion HSR showed potent in vivo activity against serine carbapenemase-producing A. baumannii and P. aeruginosa . These data support the consideration of IPM/XNW4107 for the treatment of serious infections due to these organisms in clinical trials. Disclosures: Haitao Yuan, PhD, Evopoint Biosciences Co., Ltd: Stocks/Bonds Xiao Liu, PhD, Evopoint Biosciences Co., Ltd: Stocks/Bonds Xi Chen, PhD, Evopoint Biosciences Co., Ltd: Stocks/Bonds Yuchuan Wu, PhD, Evopoint Biosciences Co., Ltd: Stocks/Bonds David P. Nicolau, PharmD, Shionogi: Grant/Research Support Kamilia Abdelraouf, PhD, Evopoint Biosciences Co., Ltd: Grant/Research Support|Venatorx Pharmaceuticals, Inc.: Grant/Research Support.